The Effects of Polyphenols on Texture and Flavor of Egg Yolk: A Molecular Docking Study - Tingting Tang; Ruyi Zhang; Cuihua Chang; Junhua Li; Luping Gu; Yanjun Yang; Yujie Su (Foods)
The effect of polyphenols on the texture and flavor of egg yolk hot gel (EY) was studied. Tea polyphenols (TP), rosmarinic acid (RE), and curcumin (CC) showed significant antioxidant properties during egg yolk processing and could effectively reduce lipid oxidation products (decreased by 68.9%, 76.4%, and 58.61%, respectively) and protein oxidation products (decreased by 47.49%, 37.47%, and 52.51%, respectively) and volatile odor components (styrene, nonanal and 1-octene-3-ol). In addition, these polyphenols enhanced the hot gel properties of the yolk, but did not significantly change the taste of the yolk. This improvement could be attributed to hydrophobic interactions, hydrogen bonds and ionic bonds formed between polyphenols and egg yolk proteins. These interactions produced a more stable structure that was less likely to unfold during heat treatment. As a result, exposure to free sulfhydryl groups, free amino acids and free fatty acids was minimized, thus reducing oxidation reactions.